2022
DOI: 10.1007/s41109-022-00465-z
|View full text |Cite
|
Sign up to set email alerts
|

Social network development in classrooms

Abstract: Group work is often a critical component of how we ask students to interact while learning in active and interactive environments. A common-sense extension of this feature is the inclusion of group assessments. Moreover, one of the key scientific practices is the development of collaborative working relationships. As instructors, we should be cognizant of our classes’ development in the social crucible of our classroom, along with their development of cognitive and/or problem solving skills. We analyze group e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Research has identified that knowledge and experience are the basis for credibility in problem solving with approaches and capabilities to translate mathematical theory into practice [24]. In China, the mathematical model exists as a mathematical competence within the curriculum, which is responsible for providing solutions to real world problems, only using mathematics whose basis for solving these problems is creativity [25], which manages to develop problem-solving skills together with cognitive skills in group tests in which they were forced to create social networks to share information and solve the evaluations [29]. The tasks for students whose approach has creative reasoning overcome the complex versions of learning in the area of mathematics and it is much better if it is programmed because it becomes of great support for the teacher and helps to improve the quality of reasoning in the classroom [39] because there is a change of attitude and surprise in the students where they only exchange glances among them when they start to solve the mathematical problems posed with this methodology of presenting problems with each situation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has identified that knowledge and experience are the basis for credibility in problem solving with approaches and capabilities to translate mathematical theory into practice [24]. In China, the mathematical model exists as a mathematical competence within the curriculum, which is responsible for providing solutions to real world problems, only using mathematics whose basis for solving these problems is creativity [25], which manages to develop problem-solving skills together with cognitive skills in group tests in which they were forced to create social networks to share information and solve the evaluations [29]. The tasks for students whose approach has creative reasoning overcome the complex versions of learning in the area of mathematics and it is much better if it is programmed because it becomes of great support for the teacher and helps to improve the quality of reasoning in the classroom [39] because there is a change of attitude and surprise in the students where they only exchange glances among them when they start to solve the mathematical problems posed with this methodology of presenting problems with each situation.…”
Section: Discussionmentioning
confidence: 99%
“…Mathematical modeling develops problem solving skills based on real environment problems, demonstrating that women (teachers) have better mathematical modeling than men (teachers) at all educational levels [28], which implies that in group work this practice has become a great help to teach those who solve less and using common sense in group evaluations, collaborative work is present to support the development of learning [29] and even more so if ICT is present as a link between mathematics learning and students because it is an accessible medium in all classrooms and educational levels, reaching the conclusion that the more ICT is used, the better academic performance is achieved at school [30].…”
Section: Mathematics In the Real World As Creativity (Social Professi...mentioning
confidence: 99%